Perceptions of a Virtual Visiting Ophthalmology Elective in the COVID-19 Era - Onyekaba, Ndidi-Amaka E.; Rosdahl, Jullia A. (Journal of Academic Ophthalmology, 2022)
Background The coronavirus disease 2019 (COVID-19) pandemic was a disruption for all aspects of medical education, especially for clinical students preparing for residency applications. Clinical rotations are essential for a student's specialty choice, especially for subspecialties such as ophthalmology where students may not get significant exposure during preclinical years. The cancellation of home and visiting ophthalmology electives due to the pandemic brought a need for newer, innovative ideas of instruction.Methods A 4-week not-for-credit virtual elective was developed at the Department of Ophthalmology for visiting medical students and was offered from August to October 2020. Visiting fourth-year medical students were paired with faculty and resident mentors for one-on-one virtual mentoring, in addition to participation in departmental conferences and research opportunities. Surveys were distributed to students and mentors, and results were analyzed using Microsoft Excel and GraphPad Prism 9.Results A total of 12 visiting fourth-year medical students participated in the virtual elective, 67% of whom did not have a home ophthalmology program. There was a significant increase in students' perception of their ophthalmology knowledge, with all of students reporting that the elective contributed to this. Students (100%) were “very satisfied” with their faculty mentors on a five-point Likert scale, with high satisfaction from faculty and resident mentors toward students also. The two required events in the elective, the journal club and case virtual conferences, were highly rated from students and mentors.Conclusion The virtual ophthalmology elective, which was developed to address medical education gaps due to the COVID-19 pandemic, was favorably viewed by all who participated. As dedicated ophthalmology instruction time has decreased over the years, it may become increasingly more important to turn to virtual resources for ophthalmology instruction and mentorship.
Keywords: ophthalmology; medical education; mentorship; COVID-19; virtual rotation